2011
DOI: 10.3855/jidc.1405
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant typhoid fever: a review

Abstract: Introduction: Multidrug-resistant typhoid fever (MDRTF) is defined as typhoid fever caused by Salmonella enterica serovar Typhi strains (S. Typhi), which are resistant to the first-line recommended drugs for treatment such as chloramphenicol, ampicillin and trimethoprimsulfamethoxazole. Since the mid-1980s, MDRTF has caused outbreaks in several countries in the developing world, resulting in increased morbidity and mortality, especially in affected children below five years of age and those who are malnourishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
116
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(141 citation statements)
references
References 79 publications
(135 reference statements)
8
116
0
2
Order By: Relevance
“…The results that are obtained from this study found in figure ( 6 ) reveal that all S .typhi isolates are sensitive (100%) for ceftriaxone ,cefepime, cefazolin, chloramphenicol, imipenem, while other S.typhi isolates were showed resistance rates (28.57%) for ampicillin , pencillin G , ciprofloxacin also S.typhi isolates were resistance (42.85%) for amikacin , (71.42%)for gentamicin ,nitrofurane and trimethoprine-sulfa and (85.71%) for tobramycin respectively . All S. typhi isolates are resistance (100%)for tetracycline and erythromycin.…”
Section: Antibiotic Sensitivity Test:-supporting
confidence: 61%
See 1 more Smart Citation
“…The results that are obtained from this study found in figure ( 6 ) reveal that all S .typhi isolates are sensitive (100%) for ceftriaxone ,cefepime, cefazolin, chloramphenicol, imipenem, while other S.typhi isolates were showed resistance rates (28.57%) for ampicillin , pencillin G , ciprofloxacin also S.typhi isolates were resistance (42.85%) for amikacin , (71.42%)for gentamicin ,nitrofurane and trimethoprine-sulfa and (85.71%) for tobramycin respectively . All S. typhi isolates are resistance (100%)for tetracycline and erythromycin.…”
Section: Antibiotic Sensitivity Test:-supporting
confidence: 61%
“…It also produces no gas when grown in Triple Sugar Iron agar, which is used to differentiate it from other Enterobacteriaceae. Despite the emergence of newer antibacterial drugs, enteric fever has continued to be a major health problem (6). S .typhi gained resistance to antibiotics like ampicillin,ceftriaxone, and co-trimoxazole, besides developing resistance to efficacious drugs like ciprofloxacin.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
“…The incidence of cardiac involvement in typhoid is variable [21][22], Myopathy can cause severe myoglobinuria and elevated CK was found in 60% of typhoid fever patients [21]. Table ( and bone marrow suppression [4]. As a result of these complication, Hematological subcutaneous abscess, subphrenic abscess and cutaneous ulcers and biochemical parameters could be afford correlation and thereby serves as indications for more reliable and diagnosis aid of the infection which could changes the necessary antibiotic therapy [9].…”
Section: Resultsmentioning
confidence: 99%
“…Typhoid fever is caused by Salmonella Enteric a Serovar Typhi, a gram-negative bacterium [4]. The organism is transmitted by the fecal-oral route; thus the disease is often associated with poor sanitation and hygiene [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…La ampicilina, cloranfenicol y trimetroprima-sulfametoxazol (TMP-SMX) fueron por muchos años los antibióticos de primera línea en el tratamiento de la fiebre entérica, pero su uso empírico e indiscriminado facilitó la generación de cepas resistentes (21,28). En 1972 se aislaron cepas resistentes al cloranfenicol en países como México, India, Vietnam y Corea (29); en 1980 se aislaron cepas resistentes a los 3 medicamentos de primera línea, dando origen a las cepas conocidas como resistentes a múltiples medicamentos (29).…”
Section: Tratamientounclassified